2010
DOI: 10.1123/ijsnem.20.1.72
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Supplementation With Ecklonia cava Polyphenol on Endurance Performance of College Students

Abstract: Ecklonia cava polyphenol (ECP) is a potent antioxidant and procirculatory agent that may contribute to improvement of endurance performance during highly intense exercise. This study evaluated the acute effect of an ECP-supplemented drink against a placebo on maximum endurance capacity and related physiological parameters. Twenty men 18-23 yr old volunteered as participants. Each performed 2 randomized trials with a 1-week interval between them. One trial was with ECP and the other with a placebo drink. Partic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
1

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 34 publications
2
41
1
Order By: Relevance
“…On the other hand, supplementation with omega fatty acids could lead to physiological and metabolic adaptations which could favor functional capacity like improved endothelial function and increased metabolic rate and fat oxidation [30,72]. Even though there is contradictory evidence regarding the effects of antioxidant intakes on exercise performance, it has been suggested that individuals with antioxidant deficiency or with high oxidative stress levels may benefit from the antioxidant treatments [73][74][75]. In support of this assertion, a recent study has shown that antioxidant supplementation decreased oxidative stress and improved physical performance in old but not in young adults [59].…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, supplementation with omega fatty acids could lead to physiological and metabolic adaptations which could favor functional capacity like improved endothelial function and increased metabolic rate and fat oxidation [30,72]. Even though there is contradictory evidence regarding the effects of antioxidant intakes on exercise performance, it has been suggested that individuals with antioxidant deficiency or with high oxidative stress levels may benefit from the antioxidant treatments [73][74][75]. In support of this assertion, a recent study has shown that antioxidant supplementation decreased oxidative stress and improved physical performance in old but not in young adults [59].…”
Section: Discussionmentioning
confidence: 99%
“…Results were relatively similar in men and women (not shown). The increase in time to exhaustion after intake of polyphenols from Ecklonia cava has been seen along with a non-significant trend towards a decrease in plasma lactate levels in college students [32]. In another study testing the effect of four-week supplementation with 800 mg of a coffeeberry formulation (polyphenol content not provided), blood lactate concentrations after 10 min of recovery following a 60-second vertical jump test were significantly reduced compared with placebo [33].…”
Section: Study 2-polyphenols and Performancementioning
confidence: 91%
“…We cannot exclude the possibility that polyphenol supplementation through its vasodilating effect may affect performance in the context of longer duration events, in which the aerobic capacity becomes a more important performance-limiting factor. Accordingly, acute supplementation with polyphenols from Ecklonia cava in 23 college student volunteers significantly increased time to exhaustion on a bicycle compared with placebo [32]. This deserves further investigation in elite athletes.…”
Section: Study 2-polyphenols and Performancementioning
confidence: 99%
“…Recently it has been found that Ecklonia cava (a species of brown alga present in the ocean of Japan and Korea) polyphenols acute preexercise supplementation induces a slight but significant increase in time to exhaustion in healthy human subjects [102]. …”
Section: Other Polyphenolsmentioning
confidence: 99%